On some interesting aspects of heavy-ion reactions studied with 7Li+11B and 9Be+9Be - Adamides, E.; Papadopoulos, C. T.; Vlastou, R.; Gazis, E. N.; Pakou, A. A.; Assimakopoulos, P. A.; Doukelis, G.; Kalfas, C. A.; Xenoulis, A. C. (HNPS Advances in Nuclear Physics, 2020)
N/A